Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Bahtera Adi Jaya Periode 2018-2022 - Satria, Rita; Imam, Didin Choerul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research was conducted to find answers regarding the influence of motivation and work discipline on employee performance at PT Bahtera Adi Jaya during the period 2018-2022, both partially and simultaneously. The research employed a quantitative associative approach. The study took place at PT Bahtera Adi Jaya with a sample size of 60 employees, determined through a non-probability sampling technique known as saturation sampling. The data used were primary data collected through observation, questionnaires, literature review, and documentation. The results of the study revealed that: 1) Motivation had a positive and significant effect on the performance of PT Bahtera Adi Jaya employees, with a calculated t-value of 2.036 > the tabulated t-value of 2.002, and a significance value of 0.046 < 0.05. 2) Work discipline had a positive and significant effect on employee performance at PT Bahtera Adi Jaya, with a calculated t-value of 2.280 > the tabulated t-value of 2.002, and a significance value of 0.026 < 0.05. 3) Motivation and work discipline, when considered simultaneously, had a positive and significant impact on the performance of PT Bahtera Adi Jaya employees, with a calculated F-value of 6.837 > the tabulated F-value of 3.16, and a significance value of 0.002 < 0.05. The coefficient of determination was 19.3%, indicating that the remaining percentage was influenced by other variables not covered in the study.